Manusia Indonesia dan Keterputusan Budaya - Muhammad Anas (el Harakah: Jurnal Budaya Islam, 2009)
Culture becomes the core and the starting point as well in building a great civilization. It includes various thinking system, cultural characteristics, social wishes, and cultural products. Ibn Khalduns concept of culture includes many more elements. Umran (culture) as human creation has a historical dimension. According to Khaldun, culture is not only a heritage from the previous culture, but also umran in becoming. Then, the principle of infisal (discontinue) becomes typical characteristics of society because the principle of separation or discontinuity views that all elements in universe are unrelated to each other. The principle of discontinuity is based on the influence of geographical condition. Besides, some sociological and cultural characteristics also influence rural and urban social lives. The finding of the concept of culture in designing Islamic culture in the future is done by considering historical aspects and factors supporting social change in Islam. This concept can be used as a reference in discussing the characteristics of Moslem society in the future and a progressive dimension of change in Islam. Budaya menjadi inti dan titik awal dalam membangun peradaban yang hebat. Ini mencakup berbagai sistem berpikir, karakteristik budaya, keinginan sosial, dan produk budaya. Konsep budaya Ibn Khaldun mencakup lebih banyak elemen. Umran (budaya) sebagai ciptaan manusia memiliki dimensi historis. Menurut Khaldun, budaya bukan hanya warisan dari budaya sebelumnya, tapi juga proses membentuk budaya. Kemudian, prinsip infisal (hentikan) muncul karena prinsip pemisahan atau diskontinuitas pandangan bahwa semua elemen di alam semesta tidak saling berhubungan satu sama lain. Prinsip diskontinuitas didasarkan pada pengaruh kondisi geografis. Selain itu, beberapa karakteristik sosiologis dan budaya juga mempengaruhi kehidupan sosial pedesaan dan perkotaan. Temuan konsep budaya dalam merancang budaya Islam di masa depan terjadi dengan mempertimbangkan aspek sejarah dan faktor pendukung perubahan sosial dalam Islam. Konsep ini bisa dijadikan referensi dalam membahas karakteristik masyarakat muslim di masa depan dan dimensi progresif perubahan dalam Islam.